The efficacy of endoscopic third ventriculostomy in children 1 year of age or younger: A systematic review and meta-analysis. (May 2020) - Zaben, M.; Manivannan, S.; Sharouf, F.; Hammad, A.; Patel, C.; Bhatti, I.; Leach, P.
Abstract: Purpose: Hydrocephalus is a major cause of morbidity in the pediatric population, with potentially severe consequences if left untreated. Two viable strategies for management of non-communicating hydrocephalus are endoscopic third ventriculostomy (ETV) and ventriculoperitoneal shunting. However, there is uncertainty over the safety and efficacy of ETV in younger infants aged 1 year or below. In this systematic review, we aim to elucidate the success rate and procedural risks of ETV in this age group. Methods: A multi-database (PubMed, Embase, Web of Science) literature search between January 1990 and April 2018 was performed in accordance with PRISMA guidelines. Eligible studies were included if they (i) examined non-communicating hydrocephalus; (ii) quantified the success/failure rates of ETV; and (iii) assessed outcomes in children 1 year of age or younger. Results: A total of 19 articles with 399 patients were eligible for inclusion. Mean age at procedure was 4.2 months (range 34 weeks gestation to 12 months), with 116 females and 143 males. Commonest underlying aetiology was congenital aqueductal stenosis (AS) (60.4%). Remaining causes included post-haemorrhagic, post-infection, Chiari malformations, malignancies and others. Overall and AS mean success rates were 51.6% and 56.5% respectively. Overall complication rate was 10.0%, consisting mainly of CSF leak, infection, and haemorrhage. Younger age was significantly associated with poorer ETV success rate when divided into <6 months and 6–12 months of age (44.4 vs 66.7%; p = 0.0007). Underlying pathology had no significant association with ETV outcome when divided into AS and other pathologies (p = 0.53). Conclusions: Age is significantly associated with ETV success rates. Pathology-dependent effects were not found in this age group. Despite a lower ETV success rate at younger ages (44.4 vs 66.7%), it offers a comparable safety profile that is independent of age. ETV remains a viable treatment option for non-communicating hydrocephalus for infants aged 1 year or younger. Highlights: Successful outcomes are seen in over half of <1 year old infants with obstructive hydrocephalus treated with ETV. Meta-analysis shows that within the <1 year age group, infants >6 months old are more likely to achieve success with ETV. No statistically significant effect of underlying pathology on outcome was demonstrated on meta-analysis.